The Effect of FUTSAL FEST Training Program on Flexibility, Endurance and Speed ​​of Futsal Players at MTs Badrussalam Indonesia - Arifin, Ahmad; Abdullah, Ahmad; Sugiarto, Dinta (Indonesian Journal of Kinanthropology (IJOK), 2025)
Background: To to be able to find out the effect of futsal fest training program on flexibility endurance and speed in futsal players MTs Badrussalam Indonesia Methods: The sample in this study was 20 male futsal players. This training was carried out for 6 weeks, namely four days a week (tuesday, wednesday, friday and sunday). Flexibility, endurance and speed ability tests were carried out before being given a training program (pretest) and after being given a training program (posttest). Results: Statistical analysis of the Paired Sample t-Test test shows that there is a significant influence on flexibility, endurance and speed in futsal players, because the significance value of the three variables is 0.000 <0.005. The study provides results that there is an influence of the FEST Futsal training program on the flexibility, endurance and speed of MTs Badrussalam Indonesia futsal players. Conclusions: The FEST Futsal training program is a training program that aims to improve the flexibility, endurance and speed of futsal players. The training program has an effect on MTs Badrussalam Indonesia futsal players by increasing their flexibility, endurance and speed. The FEST Futsal training program has a significant effect so that the training can function well in improving the physical abilities of futsal players.